2018
DOI: 10.1021/acsphotonics.8b00105
|View full text |Cite
|
Sign up to set email alerts
|

SiGeC Waveguide for All-Optical Data Switching

Abstract: The SiGeC waveguide based ultrafast all-optical switching by using the cross-absorption modulation (XAM) effect is demonstrated to perform the wavelength conversion and format inversion of a pulsed return-to-zero on–off keying (PRZ-OOK) data stream. Under the intensively optical data-bit illumination as the pump, the two-photon absorption (TPA) effect is observed to induce free carriers in the SiGeC for absorbing the power of the probe beam. This free-carrier absorption (FCA) procedure inversely modulates the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…The aforementioned description indicates that for the two channels, the ultrastrong photonic localizations near node 2 are 8.1199 × 10 5 and 3.3803 × 10 6 , respectively, and then, we set false|ψtrueprefixmax|28.1×105. The localized intensity within the DROWN can be as high as 1.03 × 10 7 W m −2 , and experiments have shown that Si‐based waveguides can withstand instant intensity up to 5.60 × 10 13 W m −2 while still remaining stable. In conclusion, via Equation the threshold control energy can be deduced, as for the designed switching, as E=102·3×1015·100×10158.1×105·1.2×10152.90×1021false(normalJfalse)…”
Section: Extraordinary Switching Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The aforementioned description indicates that for the two channels, the ultrastrong photonic localizations near node 2 are 8.1199 × 10 5 and 3.3803 × 10 6 , respectively, and then, we set false|ψtrueprefixmax|28.1×105. The localized intensity within the DROWN can be as high as 1.03 × 10 7 W m −2 , and experiments have shown that Si‐based waveguides can withstand instant intensity up to 5.60 × 10 13 W m −2 while still remaining stable. In conclusion, via Equation the threshold control energy can be deduced, as for the designed switching, as E=102·3×1015·100×10158.1×105·1.2×10152.90×1021false(normalJfalse)…”
Section: Extraordinary Switching Propertiesmentioning
confidence: 99%
“…It has been reported that the threshold control energy for metamaterial switching reaches 3 nJ and that for SiGeC waveguide switching arrives at 22 pJ . The lowest threshold control energies are achieved by microring resonators (720 fJ) and by photonic nanojets with semiconductor nanoparticles (300 fJ).…”
Section: Extraordinary Switching Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 3,4 ] In recent years, the research progress and achievements of nonlinear materials field [ 5–13 ] have also accelerated the research and improvement of all‐optical switches. [ 14–19 ] The all‐optical switch has great value in science and practice, and can be traced back to the finding of optical bistability in 1969. [ 20 ] Generally, the performance of all‐optical switching devices is evaluated by the following five basic indexes: switch efficiency/ transmission ratio, threshold energy, state transition time, switch size, and Q‐factor.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Huang et al . also employed the FCA effect in SiGeC waveguide to achieve the PRZ-OOK data format inversion up to 6 Gbit/s 22 . The all-optical logic gate is necessary to play a key role for ultrafast data processing in optical quantum computing and communication, which was mainly implemented with semiconductor optical amplifier (SOA) or periodically poled lithium niobate (PPLN) devices 23 , 24 .…”
Section: Introductionmentioning
confidence: 99%